METRICS, Model for Eliciting Team Resources and Improving Competence Structures : a socio-technical treatise on managing customer professionals in software projects for enterprise information systems - Bellini, Carlo Gabriel Porto (2006)
It is still not common in research on software quality to delve into non-technical issues. In the particular case of implementing customized information systems software (CISS), the field is also not completely aware of the importance of managing customers with a formal and objective set of measures that account for their responsibility in projects. CISS products – whose source code is ultimately developed according to each customer’s demands on core business processes – ask developers to pay unique attention to issues like competencies, culture, strategy, and resources of the client organization, as well as to the industry’ critical success factors, best practices, and prospects. The present research adds to software engineering and to organizational theory by introducing a conceptual framework (rationale) and a set of seven indicators, 27 metrics and 88 measures for improving the knowledge and the managerial practices regarding the participation of customers in CISS development.The focus is on managing the customer team (CuTe) – professionals from the client organization that contracts CISS projects, who are assigned special business and information technology (IT) roles for interacting with outsourced developers in such projects, since both customer and external (outsourced) developer teams share project authority and responsibility. Research insights and assumptions were developed throughout a six-year professional interaction with companies in a major Brazilian IT cluster; and a three-year case study within a landmark enterprise resource planning (ERP) implementation in a Brazilian university, supported by indepth interviews with key CuTe professionals in the project, provided the research with compelling data for the assembly and validation of findings. The resultant framework – formed by the rationale and the measurement instruments – is called Model for Eliciting Team Resources and Improving Competence Structures (METRICS), and it is to be used in the industry by customers and external developers to help plan, control, assess, and make historical records of CuTe design and performance in CISS projects. Academicians also benefit from the incorporation of a new perspective with which to deal with the customersupplier interaction in IT endeavors.